Réponses

Meilleure réponse !
2013-12-06T20:59:35+01:00
AB =√[ (XB-XA)²+(YB-YA)²]=√[(-2-2)²+(2-4)²]= √[(-4)²+(-2)²]=√(16+4)=√20
CD= √[(XD-XC)²+(YD-YC)²]=√[(5-(-3))²+(-5-(-1))²]=√[8²+(-4)²]=√(64+16)=√80
AD= √ [(XD-XA) ²+ (YD-YA)²]=√[5-2)²+(-5-4)²]=√[(3)²+(-9)²]=√(9+81)=10
BC=√ [(Xc-XB) ²+ (YC-YB)²]=√[(-3-(-2))²+(-1-2)²]=√[(-1)²+(-3)²]=√(1+9)=√10

AC= √ [(XC-XA) ²+ (YC-YA)²]=√[-3-2)²+(-1-4)²]=√[(-5)²+(-5)²]=√(25+25)=√50
BD=√ [(XD-XB) ²+ (YD-YB)²]=√[(5-(-2))²+(-5-2)²]=√[(7)²+(-7)²]=√(49+49)=√98

Donc AB*CD+BC*AD=40+10
√ 10=71
Et AC*BD=70
Donc AB*CD+BC*AD≈AC*BD